Proses Pendidikan Islam dalam Perspektif Ramayulis - Febriani Febriani; Rehani Rehani; Muhammad Zalnur (Edu Global : Jurnal Pendidikan Islam, 2022)
This study aims to describe the process of Islamic education in the perspective of Ramayulis. This research is descriptive qualitative with literature study method. The data collection technique used in this study is the documentation technique. This research was conducted by collecting data, analyzing, studying and exploring the thoughts of Ramayulis regarding the process of Islamic education through his works, such as books or other sources that discuss the process of Islamic education from Ramayulis. The results of this study indicate that the learning process in Islamic education is the same as education in general, but what distinguishes it is that in Islamic education the learning process and outcomes are always inherent in Islam, Islam underlies learning activities, interpreting changes that occur and animating subsequent activities. In the learning process there are several aspects that support the creation of learning as expected, 1) learning principles, 2) learning pillars, 3) learning energy and 4) forms of the learning process.